Heat-Resistant CO2 Foam for Promoting Carbon Capture and Enhanced Oil Recovery - Liu, Yali; Zhang, Chao; Wen, Quan; Li, Zhaomin; Song, Mingzhe (Frontiers in Energy Research, 2022)
Investigation of methods to effectively block the high-permeability channel and displace the residual oil in the small pores in the old oilfields is an urgent research hotspot. The heat-resistant carbon dioxide (CO2) foam with high viscoelasticity and low interfacial tension, which is suitable for improving the oil recovery of old oilfields, and at the same time aids in carbon sequestration. In this study, a suitable heat-resistant foaming agent was selected by considering the temperature resistance, plugging, and profile control as the evaluation indicators, and the heat-resistant CO2 foam was prepared. Then, the two-dimensional (2D) plate model experiment was designed to verify the feasibility of the heat-resistant CO2 foam profile control process in order to solve the problems of small sweep range and uneven sweep degree in the reservoir. The results show that the selected foaming agent (RSB-IV) still maintained a foaming volume of 375 ml at 300°C, and the interfacial tension was only 0.008 mNm−1. The prepared heat-resistant CO2 foam exhibited the best profile control effect when the gas and liquid mixed injection, the gas-liquid ratio was 1:1, and the injection volume was 4.5–5.5 PV. In the 2D plate experiment, heat-resistant CO2 foam flooding promoted the recovery of the remaining oil in the matrix, and the oil recovery was increased to 61.01%. Furthermore, by designing the CO2 gas cap, it was verified that when the volume of the gas cap was large (above 1.5 PV), the injection of the CO2 gas cap could not only effectively improve the recovery rate, but also achieve effective CO2 capture.